Utilization potential of rangeland shrubs of Bundelkhand: Areview - Singh, Kaushal; Gupta, Garima; Dobriyal, Manmohan J (Indian Journal of Agroforestry, 2022)
Rangelands in India are spread over 12.15 million ha. More than 40% of the large population of livestock still depend upon grazing in the rangelands / pastures on high altitudes, desert, semi arid/arid areas. The Bundelkhand region in central India is a typical rainfed semi-arid region. This area has degraded, undulated rocky land and constraints in arable farming, and mainly supports the growth of shrub vegetation diversity. The integration and augmentation of promising shrubs to rangeland in arid/semi-arid conditions can play important role in sustaining the rainfed and fragile ecosystem of Bundelkhand ecologically and economically. The woody perennials provides small timber, food, fodder, fuel wood, tan, dyes, fiber , ethno-medicine, live fences, windbreak, browsing reserves, fodder bank and improved fellow for various benefits. The prominent shrubs like Ziziphus oenoplea, Z. nummularia, Grewia asiatica, Opuntia dillenii, Capparis decidua, Carissa spinarum for food; Grewia flavescence, G. asiatica, Helicteres isora, Vitex nigundo, Securinega virosa and Ehratia aspera for fodder and Commiphora wightii, Helecteris isora and Barleria prionitis for medicines are few examples to mention. Shrubs are utilised for variety of purposes in Bundelkhand and a major bioresource for the livelihood options. Thus, shrubs need to be promoted for reducing the pressure on natural forest and to augment the green cover in the tropics of arid/semi-arid vis a vis increase resource base outside the forests for local population. Due to wide adaptations the shrubs have the ability to improve and reclaim the degraded wasteland to cope with the future challenges of global climate change. Sustainable scientific management and utilisation of shrub diversity is urgently needed for integrated rangeland development in Bundelkhand region. The paper reviewed the existing information & literature with analysis for the importance, preservation and management of rangeland shrubs in the semi-arid tropics of Bundelkhand.